Exploring the Efficacy of The Word Within the Word for Gifted and Typically Developing Students. Issue 2 (3rd April 2017) - Gallagher, Shelagh A.
Abstract : An exploratory study of the efficacy of The Word Within the Word tested students' abilities to recognize, use, and recall vocabulary. Ten middle school teachers and their 493 students participated. Five teachers used The Word Within the Word, and five used traditional vocabulary materials. Students completed an out-of-level sentence completion test and a test of prompted vocabulary recall. Analysis of sentence completion data revealed significant differences with moderate effect sizes, favoring students in The Word Within the Word sixth- and seventh-grade classes. Analysis of prompted vocabulary recall data revealed significant differences with moderate to large effect sizes at all grade levels, favoring The Word Within the Word classes. Results suggest that in this case, both gifted and typically developing students in classrooms using The Word Within the Word were more skilled in vocabulary recognition, use, and recall than students in classrooms using traditional methods of vocabulary instruction.